KAJIAN KARAKTERISTIK HASIL PENGGALIAN TIMBUNAN SAMPAH DI TPA KOTA KEDIRI SEBAGAI KOMPOS - harmin sulistyaning titah (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
The municipal solid waste (MSW) generation rate in Kediri was 697,768 m3 per day. The operation period of Kediri’s final disposal site (FDS) is 3-4 years. This condition provides an idea to excavate the FDS as an effort of rehabilitation, and to evaluate the fine material quality as compost. Four sampling sites were selected in the study area: site I (1 m, 3 years old), site II (2 m, 3 years old), site III (1 m, 1 year old), and site IV (2 m, 1 year old). Each sample was separated, air dried, and sieved. The highest fine material component (66,5%) was found in sampling site II. The colour of this fine material was brownish black and the odor was like soil. Characteristics of compost from all sampling sites met the compost quality standard according to SNI 19-7030-2004. Some parameters; however, exceeded the standards. These parameters werer volatile solid (> 80%), carbon (45-47%), C/N ratio (33 – 40), and faecal coli (>1000 MPN/gr). Therefore, the fine material from Kediri’s FDS could not be used as compost. The compost quality was best in FDS age of more than 3 year old and excavated from a depth of more than 2 m.